Preliminary investigations on the effect of low-pressure treatment on in vitro and in vivo growth of Penicillium sp. in oranges - Archer, John; Pristijono, Penta; Gallien, Quentin; Houizot, Laure; Bullot, Mark; Palou, Lluís; Golding, John (ISHS, 2022)
Penicillium digitatum is the major pathogen causing postharvest decay in citrus fruit and is the organism responsible for green mould. P. digitatum decay is currently managed with synthetic fungicides but there is a growing consumer need to reduce the reliance on synthetic fungicides and find alternative non-synthetic treatments. Low-pressure treatments may offer a potential solution for the storage and transport of citrus, as it is a physical treatment and does not leave any chemical residues. To test the effectiveness of low pressure storage treatments on the growth of P. digitatum, small-scale laboratory experiments were conducted with low pressure chambers. P. digitatum was grown on PDA agar plates and exposed to low pressure (4 kPa) for 3 and 6 days at 10°C before radial growth assessments in air at regular (101 kPa) atmospheres. The results showed that low pressure treatments slowed the radial growth of P. digitatum in vitro. In a further experiment on oranges, P. digitatum infected fruit were treated with low pressure (4 kPa) at 5°C for up to 22 days. This experiment also showed a reduced growth of P. digitatum in vivo. These results show the potential to control the growth of P. digitatum at low pressure treatments and further experimentation should be conducted.